Insights into vessel perforations during thrombectomy: Characteristics of a severe complication and the effect of thrombolysis - Schulze-Zachau, Victor; Rommers, Nikki; Ntoulias, Nikolaos; Brehm, Alex; Krug, Nadja; Tsogkas, Ioannis; Mutke, Matthias; Rusche, Thilo; Cervo, Amedeo; Rollo, Claudia; Moehlenbruch, Markus; Jesser, Jessica; et al. (SAGE PUBLICATIONS LTD, 2025)
Introduction: Thrombectomy complications remain poorly explored. This study aims to characterize periprocedural intracranial vessel perforation including the effect of thrombolysis on patient outcomes.
Patients and methods: In this multicenter retrospective cohort study, consecutive patients with vessel perforation during thrombectomy between January 2015 and April 2023 were included. Vessel perforation was defined as active extravasation on digital subtraction angiography. The primary outcome was modified Rankin Scale (mRS) at 90 days. Factors associated with the primary outcome were assessed using proportional odds models.
Results: 459 patients with vessel perforation were included (mean age 72.5 +/- 13.6 years, 59% female, 41% received thrombolysis). Mortality at 90 days was 51.9% and 16.3% of patients reached mRS 0-2 at 90 days. Thrombolysis was not associated with worse outcome at 90 days. Perforation of a large vessel (LV) as opposed to medium/distal vessel perforation was independently associated with worse outcome at 90 days (aOR 1.709, p = 0.04) and LV perforation was associated with poorer survival probability (HR 1.389, p = 0.021). Patients with active bleeding >20 min had worse survival probability, too (HR 1.797, p = 0.009). Thrombolysis was not associated with longer bleeding duration. Bleeding cessation was achieved faster by permanent vessel occlusion compared to temporary measures (median difference: 4 min, p < 0.001).
Discussion and conclusion: Vessel perforation during thrombectomy is a severe and frequently fatal complication. This study does not suggest that thrombolysis significantly attributes to worse prognosis. Prompt cessation of active bleeding within 20 min is critical, emphasizing the need for interventionalists to be trained in complication management.